Case Report: Pulmonary enteric adenocarcinoma harboring KRAS/TP53/APC mutations with contralateral lung metastasis: diagnostic challenges and molecular insights - Mao, Mengjie; Hu, Mengling; Tao, Qingxiu; Zuo, Zhuo; Liu, Bin (Frontiers in Oncology, 2026)
Pulmonary enteric adenocarcinoma (PEAC) is a rare subtype of lung adenocarcinoma characterized by intestinal differentiation. We report a case of synchronous bilateral PEAC in an elderly male patient, a presentation that is rarely documented in the literature. Histopathological examination revealed glandular structures resembling colorectal adenocarcinoma, with immunohistochemical positivity for CDX2, CK20, and SATB2, and negativity for TTF-1 and CK7. Molecular testing identified concurrent KRAS, TP53, and APC mutations, suggesting the activation of a colorectal-like oncogenic pathway. Following surgical resection and adjuvant chemoradiotherapy, the patient achieved short-term disease stability. This case highlights the diagnostic dilemma between primary PEAC and metastatic colorectal cancer and underscores the importance of integrated molecular and immunophenotypic profiling for accurate classification and potential targeted therapy.